Preparation and identification of anti-breast cancer cells peptides released from yak milk casein - Gu, Haofeng; Liang, Lei; Zhu, Ziwei; Mao, Xueying (Frontiers in Nutrition, 2022)
Peptides released from Yak milk casein (YMC) have multiple bioactivities, including anti-inflammation and immune-regulation, suggesting that these peptides might be able to inhibit cancer theoretically. However, the anti-cancer peptides from YMC have only been sparsely studied. Thus, the paper herein was to identify yak milk casein (YMC)-derived anti-breast cancer peptides via gel filtration, RP-HPLC and LC-ESI MS/MS for the first time. The result showed that YMC hydrolysates (YMCH) obtained by united hydrolyzation with trypsin (3 h) and alkaline protease (3 h) displayed the highest cell viability inhibition rate for MCF7 (20.74±1.39%) and MDA-MB-231 (26.73±2.87%) cells. Three peptides were identified in the RP-HPLC subfraction F3-4, and a nonapeptide (TPVVVPPFL) showed the most potent inhibitory effects on both cancer cells and displayed good gastrointestinal stability. TPVVVPPFL could induce G2-M cell cycle arrest in MCF7 cells and S cell arrest in MDA-MB-231 cells and induce apoptosis in both cancer cells. Moreover, in silico analysis indicated that the peptide had non-toxic and no inhibitory roles on P4502D6-enzyme. Together, this study shows that YMC is a good source of anti-breast cancer cells peptides.